Controlled High‐Capacity Storage of Lithium‐Ions Using Void‐Incorporated 3D MXene Architectures. Issue 14 (25th June 2020) - Min, Gyu Duk; Nam, Myeong Gyun; Kim, Dongjae; Oh, Min Jun; Moon, Joon Hyung; Kim, Woo‐Jae; Park, Juhyun; Yoo, Pil J.
Abstract: MXene, an example of 2D transition metal carbides, has recently been explored as an energy storage material for batteries or supercapacitors due to its high electrical conductivity and tunability of functional moieties. As with other 2D nano‐materials, however, attempts to harness MXene‐based electrodes have been limited by deterioration in mass transfer owing to self‐stacking and aggregation problems of MXenes. Here, means of creating 3D‐structured MXene films having voids of controlled size using templated co‐assembly between MXene nanosheets and monodisperse colloidal particles are presented. Using a 3D‐structured MXene‐only film incorporating microscale voids as a thin‐film electrode for Li‐ion batteries yield an initial specific capacity of 435.4 mAh g −1 at a current density of 0.01 A g −1 and highly extended cyclic stability persisting 1200 cycles, approaching the reported theoretical capacity of MXene even without employing any binder or conductive species. Electrochemical analyses reveal that the improved specific capacity is attributable to enhanced contribution of pseudo‐capacitive Li‐storage compared to diffusion‐mediated capacity, as incorporated voids tend to facilitate ionic transport into the interior region of the MXene films. Therefore, this work offers a concrete understanding to realize improved electrochemical performances of 2D nanomaterial‐based electrodes, especially in the form of free‐standing thin films. Abstract : 3D‐void‐incoporated MXene films are used as a thin‐film anode for Li‐ion battery without employing any binder or conductive species to exhibit highly improved specific capacity. Electrochemical analyses reveal that the improved capacity performance is attributed to increased contribution of the pseudo‐capacitive Li‐storage compared to diffusion‐mediated capacity, as the incorporated pore scale increases.